2014
DOI: 10.1108/mi-10-2013-0051
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of photovoltaic solar modules dark properties after exposition to electrical reverse stress current inducing thermal effect

Abstract: Purpose -The purpose of this paper is to investigate the dark properties as a function of reverse current induced defects. Dark characteristics of solar modules are very essential in the understanding the functioning of these devices. Design/methodology/approach -Reverse currents were applied on the photovoltaic (PV) modules to create defects. At several time intervals, dark characteristics along with surface temperature were measured. Findings -Current-voltage (I-V) and capacitance-voltage (C-V) characteristi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…These studies however tackled the problem in the dark conditions. Another study contributed to the effect of heat on the performance of photovoltaic cells and modules, where the heat resulted in the occurrence of reverse currents affecting the I-V characteristics [9].…”
Section: Introductionmentioning
confidence: 99%
“…These studies however tackled the problem in the dark conditions. Another study contributed to the effect of heat on the performance of photovoltaic cells and modules, where the heat resulted in the occurrence of reverse currents affecting the I-V characteristics [9].…”
Section: Introductionmentioning
confidence: 99%
“…The authors in [36,37] demonstrated microscopic damages (and hot spots) after making flow a minimal reverse current of 10 mA for 10 min through shaded (amorphous silicon) PVMs. Additionally, in [37], a dramatic drop in the shunt resistance (almost a short circuit) for similar test conditions was demonstrated. The authors also showed that the effect is faster under greater temperatures (70 • C) than ambient ones.…”
Section: Reverse Current Degradationmentioning
confidence: 99%